2016
DOI: 10.1016/j.clinph.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Finger force changes in the absence of visual feedback in patients with Parkinson’s disease

Abstract: Objectives We investigated the unintentional drift in total force and in sharing of the force between fingers in two-finger accurate force production tasks performed without visual feedback by patients with Parkinson’s disease (PD) and healthy controls. In particular, we were testing a hypothesis that adaptation to the documented loss of action stability could lead to faster force drop in PD. Methods PD patients and healthy controls performed accurate constant force production tasks without visual feedback b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…Links between this phenomenon and the stability of produced mechanical variables have been hypothesized earlier (Ambike et al 2015, 2016) and supported by observations in patients with Parkinson’s disease (Vaillancourt et al 2001; Jo et al 2016). In earlier studies, this phenomenon was observed only for the explicitly instructed normal force component in pressing tasks.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Links between this phenomenon and the stability of produced mechanical variables have been hypothesized earlier (Ambike et al 2015, 2016) and supported by observations in patients with Parkinson’s disease (Vaillancourt et al 2001; Jo et al 2016). In earlier studies, this phenomenon was observed only for the explicitly instructed normal force component in pressing tasks.…”
Section: Introductionsupporting
confidence: 70%
“…Their existence has been supported by the phenomenon of anticipatory synergy adjustment (ASA; Olafsdottir et al 2005), because ASAs occur when performance – and therefore NV1 – remains unchanged, so another control process should be responsible for the ASAs, possibly associated with NV2. Recent observations in neurological patients have also shown dissociation between synergy indices and ASAs: while patients with subcortical disorders show both reduced synergy indices and smaller ASAs (Park et al 2012, 2013; Jo et al 2015), patients with mild cortical stroke show unchanged synergy indices and significantly smaller ASAs (Jo et al 2016). …”
Section: Discussionmentioning
confidence: 98%
“…However, within our scheme, the drift in performance is not due to deterioration of memory on RC but to its natural drift during continuous task performance without salient sensory feedback. In fact, a pilot study has shown that resting for a comparable time does not lead to a force drop (Jo et al 2016) suggesting that the subjects do not show force drift because they forget the RC (or the corresponding force magnitude).…”
Section: Origins Of Unintentional Change In Performancementioning
confidence: 99%
“…For various quantities (means and amplitudes for the cyclic F-task, and mean force for the continuous F-task), exponential functions of the form F(t) = a × e −t/τ + c were fit to the data, where t is time, and τ is the time constant (seconds) of the exponential change in F. This particular functional form was motivated by earlier studies (e.g., Ambike et al 2015;Jo et al 2015) as well as by the typical exponential forms of relaxation processes in physical systems. Note that at the time of feedback removal (t = 0), the variable value is given by F(0) = a + c, and at the steady state (t = ∞), it is F(∞) = c. Thus, a estimates the net drop in F. These fits were performed for data averaged across subjects.…”
Section: Analysis Of the Continuous Tasksmentioning
confidence: 99%
“…Indeed, after the original publication, only a few studies explored this phenomenon (Vaillancourt et al 2001, Vaillancourt and Russell 2002, Shapkova et al 2008, and it was also invoked in studies of "slacking", a phenomenon observed in stroke survivors who show a drop in effort when helped by an external device (Reinkensmeyer et al 2009). The original interpretation that the phenomenon reflected a limitation in the working memory was indirectly supported by a study of patients with Parkinson's disease (Vaillancourt et al 2001) and has not been challenged until recently Jo et al 2015).…”
Section: Unintentional Force Drift: Possible Causesmentioning
confidence: 99%